5'-O-(2-Isopropoxyprop-2-yl)-protected Phosphoramidite Building Blocks in the Liquid Phase Oligonucleotide Synthesis - Liang Zehong; Rosenqvist Petja; Pajuniemi Ella; Ora Mikko; Heinonen Petri; Virta Pasi; Oivanen Mikko (WILEY-V C H VERLAG GMBH, 2025)
5'-O-(2-isopropoxyprop-2-yl) (IIP)-protection was introduced to 5’-OH function of nucleosides in high yields by an acid-catalysed transacetalization with 2,2-diisopropoxypropane. The applicability of this temporal 5’-O-protecting group was demonstrated in the liquid phase oligonucleotide synthesis (LPOS) using the corresponding phosphoramidite building blocks (dA, dG, dC and dT) and a tetrapodal precipitative soluble support. Standard protecting groups were used on nucleobases. Tetrazole as an activator, followed by oxidation using m-chloroperbenzoic acid, was used for the coupling. The IIP was shown to be a capable choice to the 5’-O protection in solution phase synthesis. It could be readily removed with formic acid (t1/2<10 s in 6 % HCOOH in dichloromethane/methanol (2/1) at RT), resulting in volatile byproducts (acetone and isopropanol).